2021
DOI: 10.1016/j.eclinm.2021.100776
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based host biomarker diagnostics in active case finding for pulmonary tuberculosis: A diagnostic case-control study

Abstract: Background There is a need to identify scalable tuberculosis screening strategies among high burden populations. The WHO has identified a non-sputum-based triage test as a development priority. Methods We performed a diagnostic case-control study of point-of-care C-reactive protein (CRP) and Prototype-Xpert-MTB-Host-Response (Xpert-MTB-HR) assays in the context of a mass screening program for tuberculosis in two prisons in Brazil. All incarcerated individuals irrespecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…The Sweeney3 signature was most strongly associated with HIV risk in unadjusted and adjusted analyses, and in the LTBI-negative, but not the LTBI-positive group. This three-gene set predicts the presence of active TB disease versus LTBI with better accuracy (86% sensitivity, 86% specificity) than most combinations of clinical prediction tools, and with similar sensitivity to GeneXpert-MTB RIF sputum tests [ 42 , 43 ]. Because the three genes, GBP5, DUSP3, and KLF2, are associated with macrophage regulation and other immune pathways [ 44 46 ], this gene set may detect a high-risk systemic immune status, provoked by genital or gastrointestinal infection or altered microbiome composition, which could also be differentially associated with LTBI status.…”
Section: Discussionmentioning
confidence: 99%
“…The Sweeney3 signature was most strongly associated with HIV risk in unadjusted and adjusted analyses, and in the LTBI-negative, but not the LTBI-positive group. This three-gene set predicts the presence of active TB disease versus LTBI with better accuracy (86% sensitivity, 86% specificity) than most combinations of clinical prediction tools, and with similar sensitivity to GeneXpert-MTB RIF sputum tests [ 42 , 43 ]. Because the three genes, GBP5, DUSP3, and KLF2, are associated with macrophage regulation and other immune pathways [ 44 46 ], this gene set may detect a high-risk systemic immune status, provoked by genital or gastrointestinal infection or altered microbiome composition, which could also be differentially associated with LTBI status.…”
Section: Discussionmentioning
confidence: 99%
“… Triage Collection method and not a test itself - Studies are few and heterogenous, no pooled performance estimates exist - Ultra applied to a single swab had a sensitivity of 88% in outpatients 41 but only 43% sensitivity when used for active case finding in a prison 40 - TB-LAMP 42 applied to oral swabs had sensitivities ranging from 33-50% - FLOQSwabs (Copan Italia) preferred 41 - Self-swabbing, comparable to health worker-administered swabs for other pathogens 44 , appears feasible - Potential for paediatric TB 43 - Insufficient Mtb may be recovered from swabs in patients with low sputum bacillary load 40 - Performance of novel assays (e.g., next-generation LAM and NAATs unknown) may overcome sensitivity limitations associated - Optimal number of swabs, swab design, and the processing method are under evaluation and may improve the release of material from swabs -No tests purpose-built for tongue swabs yet exist Blood Host transcriptome mRNA blood signatures associated with the immune system's response to Mtb have shown promise for diagnosis. 68 Triage Xpert Host Response (Cepheid) - A multicentre study showed 90% sensitivity and 86% specificity 64 -Other studies have shown lower specificities (26% 101 , 53% 102 ) at >90% sensitivity - Limited data with small numbers of cases, however, multicentre studies are emerging - Xpert HR has the most data available - RNA is labile and, for Xpert HR, time from blood collection to testing must be <30 min and stabilisation agents may be required - Cost unclear, but likely high - Potential utility treatment response monitoring, management of diseases other than TB (signature-positive patients without TB could have other infections 95 ), and false-positive TB PCR results 65 , which are frequent in people with previous TB 68 , 84 , 103 - Signatures (including Sweeney3 in Xpert HR) measured using ultra-sensitive methods (sequencing, Nanostring) 68 struggle to meet WHO TPPs 65 , 66 ...…”
Section: Overview Of Diagnostic Technologies and Tests By Specimen Typementioning
confidence: 99%
“…This three-gene set predicts the presence of active TB disease versus LTBI with better accuracy (86% sensitivity, 86% specificity) than most combinations of clinical prediction tools, and with similar sensitivity to GeneXpert-MTB RIF sputum tests. [43,44] Because the three genes, GBP5, DUSP3, and KLF2, are associated with immune signaling pathways and macrophage regulation [45][46][47], this gene set may detect a high-risk systemic immune status related to genital or gastrointestinal infection or altered microbiome composition, which could also be differentially associated with LTBI status. In contrast, the RESPONSE5 profile evaluates differential gene expression that predicts cure after TB treatment, wherein a high score represents higher innate immune activation [28], and higher scores were associated with lower odds of HIV acquisition in this cohort.…”
Section: Discussionmentioning
confidence: 99%